Adjustable Thermal Expansion Properties in Zr2MoP2O12/ZrO2 Ceramic Composites - Liu, Hongfei; Sun, Weikang; Xie, Xiang; Yang, Lu; Zhang, Zhiping; Zhou, Min; Zeng, Xianghua; Chen, Xiaobing (Frontiers in Chemistry, 2018)
Zr2MoP2O12/ZrO2 composites were successfully synthesized by the solid state reaction method in attempt to fabricate the near-zero thermal expansion ceramics. The phase composition, microstructure and thermal expansion property of Zr2MoP2O12/ZrO2 composites with different mass ratios were investigated using X-ray diffraction, scanning electron microscopy and thermal mechanical analysis. Results indicate that Zr2MoP2O12/ZrO2 composites can be prepared by pre-sintering at 500 °C for 3 h and then sintering at 1050 °C for 6 h. The resulting Zr2MoP2O12/ZrO2 composites consisted of orthorhombic Zr2MoP2O12 and monoclinic ZrO2. With increasing content of Zr2MoP2O12, the Zr2MoP2O12/ZrO2 ceramics became more compact and the coefficient of thermal expansion decreased gradually. Zr2MoP2O12/ZrO2 composites show an adjustable coefficient of thermal expansion (CTE) from 5.57×10-6 K-1 to -5.73×10-6 K-1 by changing the mass ratio of Zr2MoP2O12 and ZrO2. The Zr2MoP2O12/ZrO2 composite with a mass ratio of 2:1 showed near zero thermal expansion, and the average linear thermal expansion coefficient is measured to be 0.0082×10-6 K-1 in the temperature range from 25 °C to 700 °C.